2006
DOI: 10.1126/science.1128439
|View full text |Cite
|
Sign up to set email alerts
|

A Plant Peptide Encoded by CLV3 Identified by in Situ MALDI-TOF MS Analysis

Abstract: The Arabidopsis CLAVATA3 (CLV3) gene encodes a stem cell-specific protein presumed to be a precursor of a secreted peptide hormone. Matrix-assisted laser desorption/ionization-time-of-flight mass spectrometry (MALDI-TOF MS) applied to in situ Arabidopsis tissues determined the structure of a modified 12-amino acid peptide (MCLV3), which was derived from a conserved motif in the CLV3 sequence. Synthetic MCLV3 induced shoot and root meristem consumption as cells differentiated into other organs, displaying the t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

12
368
1
6

Year Published

2007
2007
2023
2023

Publication Types

Select...
5
4

Relationship

1
8

Authors

Journals

citations
Cited by 441 publications
(412 citation statements)
references
References 20 publications
12
368
1
6
Order By: Relevance
“…Therefore, a better explanation to reconcile these findings would be that in vivo AtPep2,4,5 need proteolytic processing at their C-terminal sides for maturation. Maturation of plant signaling peptides through proteolytic cleavage of both N-and C-terminal sides has been demonstrated in the CLE family of peptides [38]. Currently, little is known about the dynamics of PROPEP maturation, but it is possible that this might be a rapid process.…”
Section: Discussionmentioning
confidence: 99%
“…Therefore, a better explanation to reconcile these findings would be that in vivo AtPep2,4,5 need proteolytic processing at their C-terminal sides for maturation. Maturation of plant signaling peptides through proteolytic cleavage of both N-and C-terminal sides has been demonstrated in the CLE family of peptides [38]. Currently, little is known about the dynamics of PROPEP maturation, but it is possible that this might be a rapid process.…”
Section: Discussionmentioning
confidence: 99%
“…Biological functions of several CLE peptides have been revealed. For example, CLV3 and CLE40 are responsible for shoot and root apical meristem maintenance, respectively [9,11,12]. CLV3 is perceived by three different receptors or putative receptors, CLAVA-TA1 (CLV1), CLAVATA 2 (CLV2)-CORYNE (CRN), and RPK2/TOAD2, to limit stem cell size by restricting the expression of a homeodomain transcription factor, WUSCHEL (WUS), via a negative feedback loop [13][14][15][16][17][18].…”
Section: Introductionmentioning
confidence: 99%
“…PUB4 functions in the SAM MCLV3 was able to mimic the CLV3 over-expression phenotype when treated to wild type plants and induces SAM termination 9 . On the other hand, pub4 mutants were able to maintain SAM activity and to induce bolting on the media containing MCLV3 ( Fig.…”
mentioning
confidence: 99%
“…[6][7][8]15 Previously, we have shown that a synthetic CLV3 peptide, MCLV3 could be a useful tool for investigating downstream components of the CLV signaling pathway. 7,9 Here we report the defects of SAM in a recently identified MCLV3 resistant mutant, pub4, 10 and discuss the possible relationship of its causal gene with the CLV signaling pathway.…”
mentioning
confidence: 99%